Combination of Herbal Therapy Compress Ball and Pelvic Tilt Exercise for Low Back Pain in Third Trimester Pregnant Women - Emi Br Barus; Meli Doloksaribu; Desi Br Sembiring (Sean Institute, 2023)
Pregnancy is a normal process that produces a series of physiological and psychological changes in pregnant women. During pregnancy there are changes in anatomical, physiological and biochemical adaptations in the body of pregnant women. Parallel to the gradual increase in body weight during pregnancy and central redistribution there are hormonal influences on the ligament structure. These two factors change the posture of pregnant women to make it lordosis which will then be at risk of back pain. Data analysis using analysis used is the Paired t-Test. Result: The significance value of the pre test and post test is 0.001, meaning that there is a difference in Low Back Pain for Pregnant Women in the Third Trimester before and after the intervention. Thus it can be concluded that there is an effect of giving a combination of Herbal Therapy Compress Ball and Pelvic Tilt Exercise